Mengupas makna syukur dari sudut pandang remaja awal - Adzanishari Mawaddah Rahmah; Zainal Abidin; Fitri Ariyanti Abidin (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2022)
Studies showed that gratitude can be used as an approach to prevent adolescent mental health problems. The concept of gratitude that was used generally refered to a concept from Western culture or a concept applied to adults. This study aimed to explore the concept of gratitude in early adolescents using qualitative methods. Respondents consisted of 22 boys and 45 girls aged 12 to 15 years. The instrument used was open-ended questionnaire about the meanings, objects, forms of expression, along with the affective sides of gratitude. Data were analyzed using thematic analysis. The result of this study indicated that the concept of gratitude interpreted by early adolescents was represented by four major categories, namely thanking and praising God, accepting, enjoying, and appreciating. The object of gratitude were gifts of God, valuable objects, academic achievements, and social relations. Whereas expressions of gratitude were expressed by praying, verbalizing, worshiping God, developing oneself, and doing positive things to others. These finding showed that the concept of gratitude for early adolescents in Indonesia is closely related to divinity and morals but still intact with the characteristics of adolescent development.